2016
DOI: 10.1111/jcal.12133
|View full text |Cite
|
Sign up to set email alerts
|

Using U‐Pace instruction to improve the academic performance of economically disadvantaged undergraduates

Abstract: This study was undertaken to evaluate whether the student success associated with the U-Pace instructional approach, which integrates mastery-based learning with proactive instructor support in an online learning environment, would replicate for both economically disadvantaged students and students who are not economically disadvantaged. Undergraduates were enrolled in U-Pace (intervention) or comparison sections of a gateway course at two universities with different learning management systems. Course content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…Consequently, the efficacy of U‐Pace instruction for at‐risk students and students not at‐risk could be determined. The results not only confirm previous findings of greater academic success and greater learning associated with U‐Pace instruction (Fleming et al, ; Reddy et al, ; 2013) but also clearly demonstrate that U‐Pace instruction produces greater learning and greater academic success than conventional face‐to‐face instruction. Further, the findings of this research reveal that these student outcomes generalize across courses in two disciplines for both students at‐risk for college noncompletion and students not at‐risk, providing strong support for the efficacy of U‐Pace instruction.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Consequently, the efficacy of U‐Pace instruction for at‐risk students and students not at‐risk could be determined. The results not only confirm previous findings of greater academic success and greater learning associated with U‐Pace instruction (Fleming et al, ; Reddy et al, ; 2013) but also clearly demonstrate that U‐Pace instruction produces greater learning and greater academic success than conventional face‐to‐face instruction. Further, the findings of this research reveal that these student outcomes generalize across courses in two disciplines for both students at‐risk for college noncompletion and students not at‐risk, providing strong support for the efficacy of U‐Pace instruction.…”
Section: Discussionsupporting
confidence: 88%
“…Two randomized controlled trials (RCTs) were conducted to rigorously evaluate the efficacy of U‐Pace instruction in the contexts of introductory sociology and introductory political science. Although previous research has not examined U‐Pace instruction's efficacy in a gateway course other than introductory psychology (Fleming et al, ; Reddy et al, ), U‐Pace instruction's empirical grounding supports the assertion that U‐Pace instruction would produce greater academic success for students across course/discipline. Individualized mastery learning courses have been used to improve student outcomes in diverse subject areas (e.g., Block & Burns, ; Kulik, Kulik, & Bangert‐Drowns, ; Rae & Samuels, ; Svenningsen & Pear, ), and proactive instructor support could be applied in a variety of academic disciplines and educational settings.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In Fleming et al (2016), random assignment of undergraduates to instructional condition occurred at one of the two institutions in the study, but as in the two previous studies, U-Pace was only compared to face-to-face instruction. It was found that U-Pace instruction was associated with a greater percentage of final grades of A or B at both universities, located in geographically distinct areas, but the improvement in rate of content mastery for U-Pace students across the semester was found at only one of the two institutions.…”
Section: The Current Studymentioning
confidence: 99%